Digital Pop-Up Book Media on Ecosystem Material Oriented On Bali’s Local Wisdom to Improve Elementary School Students Science Learning Achievement - Dewi, I Gusti Agung Ayu Kirana; Sanjaya, Dewa Bagus; Candiasa, I Made (Universitas Pendidikan Ganesha, 2025)
The lack of utilization of interesting and innovative learning media in ecosystem material causes low interest and learning achievement in students. This development research aims to produce a design and create digital Pop-Up Book media for ecosystem materials oriented towards Balinese local wisdom, to improve the learning achievement of fifth-grade elementary school students in science and natural sciences, making it feasible, practical, and effective. The subjects of this research included experts (two lecturers with a Master's degree in Elementary Education), 12 fifth-grade elementary school students for one-on-one and small group tests, 10 teachers for practicality tests, and 28 fifth-grade students for limited tests to assess the practicality and effectiveness of the digital Pop-Up Book media. The development model used in this research is the ADDIE model. The feasibility test of content, language, presentation, and graphics of the material and media used the National Education Standards Agency (BSNP) assessment instrument. Furthermore, the practicality test was carried out using the User Experience Questionnaire (UEQ) instrument. Effectiveness testing was conducted using a pre-experimental design with a one-group pretest-posttest approach. Science and natural science learning achievement data were collected through tests and analyzed using a one-tailed t-test. Based on the analysis results, this media is feasible and practical to use in learning. The t-test results show an increase in the learning achievement of fifth-grade elementary school students in science using digital Pop-Up Books oriented towards Balinese local wisdom in elementary school. It is concluded that digital Pop-Up Books oriented towards Balinese local wisdom can be effectively used in learning activities, as they facilitate students' learning.